The Analysis of Metaphorical Expression in Billie Eilish’s Songs - Tegar Arif Topan (Asosiasi Dosen Muda Indonesia, 2025)
A metaphor is a kind of figurative language. Songwriters use metaphors to facilitate listeners' comprehension of song lyrics' meanings. The objective of this study was to examine the kinds, meanings, and functions of metaphors in three chosen songs by Billie Eilish. The study was conducted using a descriptive qualitative technique. The study methodology was executed in three phases: data gathering techniques, data analysis techniques, and presentation strategies for the analysis outcomes. Data collection was conducted via non-participant methods and note-taking approaches. This study analyzes the lyrics of three selected Billie Eilish songs: